UJI AKTIVITAS ANTIHIPERTENSI TANAMAN TUMPANG AIR (PEPEROMIA PELLUCIDA (L.) KUNTH) TERHADAP TIKUS WISTAR JANTAN HIPERTENSI YANG DIINDUKSI DEKSAMETASON - Fikriyah, Riadhotul
Non-communicable diseases are the most widely cause of death. Particularly, cardiovascular diseases make up most of the non-communicable diseases that caused death. Hypertension is one of the most significant risk factor of cardiovascular diseases. The extract of pepper elder (Peperomia pellucida (L.) Kunth) shows ACE-inhibiting activities and hypotension effect on normotensive rats. The purpose of this study was to determine the antihypertensive activity of pepper elder in dexamethasone induced hypertensive rats. The animals in this research were injected by 0.5 mg/kg of bw dexamethasone subcutaneously. The antihypertensive effects of concentrated pepper elder juice of was determined based on the systolic and diastolic blood pressure. The blood pressures were measured by non-invasive (CODA®) tail-cuff blood pressure system and ware measured before induction, after induction, and throughout therapy until day 6. The standard group was given 13.5 mg/kg of bw of captopril. The test groups were given 15, 30, and 60 mg/kg of bw of the concentrated pepper elder juice. There was a significant (p<0.05) increase in systolic and diastolic blood pressure in all induced animals. The average systolic blood pressure reduction after administration of 15, 30, and 60 mg/kw of bw of the concentrated pepper elder juice were 20.0, 49.5, and 49.1 mmHg respectively, while the diastolic blood pressure reduction were 10.8, 39.5, 49.7 mmHg. Blood pressure reduction of 30 and 60 mg/kg of bw of pepper elder and 13.5 mg/kg of bw of captopril were similar (p>0.05). The concentrated pepper elder juice 30 and 60 mg/kg of bw had antihypertensive effects.